2019
DOI: 10.1002/iub.2121
|View full text |Cite|
|
Sign up to set email alerts
|

Mass spectrometry‐based proteomic analysis of FSCN1‐interacting proteins in laryngeal squamous cell carcinoma cells

Abstract: Fascin actin-bundling protein 1 (FSCN1) is an evolutionarily conserved actinbundling protein that plays a critical role in cell migration, motility, adhesion, and cellular interactions. Although multiple clinical studies have implicated the expression of FSCN1 in laryngeal squamous cell carcinoma (LSCC) progression, the precise mechanism of FSCN1 in the process has not been clearly elucidated. To define FSCN1 function, we characterized FSCN1-interacting proteins in LSCC cells by immunoprecipitation followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…Several studies reported an elevated fascin 1 protein expression at the tumor invasive borders in esophageal, gastric and oral carcinomas [31][32][33]. Overex-pression of fascin 1 promotes an aggressive clinical course in patients with HNSCC [8,15,16,28,37,38]. Here, we found a significant correlation between fascin 1 protein expression and HNSCC-related mortality in both univariate and multivariate analyses.…”
Section: A C K N O W L E D G E M E N T Ssupporting
confidence: 63%
“…Several studies reported an elevated fascin 1 protein expression at the tumor invasive borders in esophageal, gastric and oral carcinomas [31][32][33]. Overex-pression of fascin 1 promotes an aggressive clinical course in patients with HNSCC [8,15,16,28,37,38]. Here, we found a significant correlation between fascin 1 protein expression and HNSCC-related mortality in both univariate and multivariate analyses.…”
Section: A C K N O W L E D G E M E N T Ssupporting
confidence: 63%
“…There are reports indicating that fascin might have actin‐bundling independent functions in cancer [128]. Fascin has been shown to interact with a number of proteins other than F‐actin [24,123,129–131]. Although the functional implication of these interactions in cancer metastasis is largely unclear, we suspect that fascin might have much broader roles in cancer metastasis than promoting cancer cell migration and invasion.…”
Section: Perspective and Future Directionmentioning
confidence: 94%
“…In addition to the above interaction partners, various proteins have been found to physiologically interact with FSCN1. [36][37][38][39][40][41] However, it has not been established if these interactions regulate the actinbundling activity of FSCN1.…”
Section: Regulation Of Fscn1 Activitymentioning
confidence: 99%